Quincke Triad and Hepatic Artery Pseudoaneurysm Presenting to the Emergency Department: A Case Report - Courtney Wham; Daria Nicke; Justin Burman; Robert Meller; Premal Trivedi; Andra Farcas (Clinical Practice and Cases in Emergency Medicine)
Introduction: Hepatic artery aneurysms are exceedingly rare, often asymptomatic, and usually diagnosed when patients present with complications such as rupture or bile duct obstruction. Case Report: This report describes a 70-year-old female who presented to the emergency department with Quincke triad (epigastric pain, obstructive jaundice, and gastrointestinal bleeding) and was diagnosed with multiple hepatic artery pseudoaneurysms with a thrombosed fistulous connection to the biliary system. She was treated effectively with extensive embolization and biliary stenting. Conclusion: This case underscores the importance of early diagnosis and highlights the role of multidisciplinary intervention in preventing life-threatening complications from hepatic artery aneurysms.